Blockade of IL-6/IL-6R Signaling Attenuates Acute Antibody-Mediated Rejection in a Mouse Cardiac Transplantation Model - Ma, Maolin; Sun, Qipeng; Li, Xiujie; Deng, Gengguo; Zhang, Yannan; Yang, Zhe; Han, Fei; Huang, Zhengyu; Fang, Youqiang; Liao, Tao; Sun, Qiquan (Frontiers in Immunology, 2021)
Acute antibody-mediated rejection (AAMR) is an important cause of cardiac allograft dysfunction, and more effective strategies need to be explored to improve allograft prognosis. Interleukin (IL)-6/IL-6R signaling plays a key role in the activation of immune cells including B cells, T cells and macrophages, which participate in the progression of AAMR. In this study, we investigated the effect of IL-6/IL-6R signaling blockade on the prevention of AAMR in a mouse model. We established a mouse model of AAMR for cardiac transplantation via presensitization of skin grafts and addition of cyclosporin A, and sequentially analyzed its features. Tocilizumab, anti-IL-6R antibody, and recipient IL-6 knockout were used to block IL-6/IL-6R signaling. We demonstrated that blockade of IL-6/IL-6R signaling significantly attenuated allograft injury and improved survival. Further mechanistic research revealed that signaling blockade decreased B cells in circulation, spleens, and allografts, thus inhibiting donor-specific antibody production and complement activation. Moreover, macrophage, T cell, and pro-inflammatory cytokine infiltration in allografts was also reduced. Collectively, we provided a highly practical mouse model of AAMR and demonstrated that blockade of IL-6/IL-6R signaling markedly alleviated AAMR, which is expected to provide a superior option for the treatment of AAMR in clinic.